2000
DOI: 10.5962/bhl.part.80119
|View full text |Cite
|
Sign up to set email alerts
|

Rudolphiella szidati sp. n. (Proteocephalidea: Monticelliidae, Rudolphiellinae) parasite of Luciopimelodus pati (Valenciennes, 1840) (Pisces: Pimelodidae) from Argentina with new observations on Rudophiella lobosa (Riggenbach, 1895)

Abstract: Rudolphiella szidati sp. n. (Proteocephalidea: Monticelliidae, Rudolphiellinae) parasite of Luciopimelodus pati (Valenciennes, 1840) (Pisces: Pimelodidae) from Argentina with new observations on Rudolphiella lobosa (Riggenbach, 1895

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…We also observed similar polar projections in Brooksiella praeputialis (Rego, Santos et Silva, 1974) (de Chambrier et al 2004) and in Rudolphiella spp. (Gil de Pertierra and de Chambrier 2000). However, the embryophore layer of those species is distinct, presenting an elongated polar wall.…”
Section: Parasite Speciesmentioning
confidence: 99%
“…We also observed similar polar projections in Brooksiella praeputialis (Rego, Santos et Silva, 1974) (de Chambrier et al 2004) and in Rudolphiella spp. (Gil de Pertierra and de Chambrier 2000). However, the embryophore layer of those species is distinct, presenting an elongated polar wall.…”
Section: Parasite Speciesmentioning
confidence: 99%
“…More recently some authors (de Chambrier and Vaucher 1997, 1999, 1999, Gil de Pertierra and de Chambrier 2000, Zehnder and de Chambrier 2000, Cañeda-Guzmán et al 2001, de Chambrier 2001, de Chambrier et al 2003 have reported (at the light microscopical level) that the secondary osmoregulatory canals terminate beneath the tegument, i.e. they do not open outside, as reported earlier by Riggenbach (1895).…”
mentioning
confidence: 64%
“…It is strongly recommended to revise the structure of the uterus and living eggs or eggs preserved outside proglottides. This approach could provide important taxonomic information and is successfully applied, e.g., in studies of Proteocephalus (Gil de Pertierra and de Chambrier 2000, De Chambrier et al 2004 and rarely also in some other cestode groups (Georgiev and Gardner 2004). Findings from Slovakia confirm that Anomotaenia should comprise only species with a reticulate uterus and eggs having filaments, as it is characteristic for the typespecies A. microrhyncha.…”
mentioning
confidence: 70%